THE BASIS OF CONSULTING SERVICES IN MANAGEMENT OF PRODUCTION - В. І. Захарченко (Ринкова економіка: сучасна теорія і практика управління, 2018)
A systematic approach is proposed for the identification and selection of methods for increasing productivity, reducing production costs and improving the quality so that the consultant’s approach to problem solving is more focused on the problem than on the method. The subject of consulting services in the field of modern production management is products, production methods, and human factor. The discussed issues are contained within the framework of modern innovation production.